1998
DOI: 10.1111/j.1365-2052.1998.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Report of the first workshop on the genetic map of bovine chromosome 1

Abstract: SummaryA report of the first workshop on the genetic map of bovine chromosome 23 (BTA23) is given. Five laboratories contributed data from 29 loci, including a total 11586 informative genotypes. The combined pedigrees represented 1930 potentially informative meioses. Eighteen of the 29 loci were common to two or more data sets and were used to construct a framework linkage map of BTA23. Twelve of the 18 could be ordered on the linkage map with a likelihood ratio of greater than 100O:l. Thus, a low resolution c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…Chromosomal workshops have revealed that the IBRP female maps are larger than the male maps for chromosomes 1, 10, and 23, whereas the male maps are larger than the female MARC and TAMU maps for these chromosomes Taylor et al 1997Taylor et al , 1998. Some of these differences are likely to be due to variation in recombination rates between individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosomal workshops have revealed that the IBRP female maps are larger than the male maps for chromosomes 1, 10, and 23, whereas the male maps are larger than the female MARC and TAMU maps for these chromosomes Taylor et al 1997Taylor et al , 1998. Some of these differences are likely to be due to variation in recombination rates between individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a number of cattle linkage maps exist that have been developed with different sets of families and different sets of loci (Ma et al 1996;Barendse et al 1997;Kappes et al 1997). As a consequence, some difficulties are experienced in moving between the cattle maps to predict relative positions of loci, and several cattle mapping workshops have been held to address these issues (Taylor et al 1998;Casas et al 1999;Gu et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, there are indications of sex-specific differences in recombination maps for some chromosomes, e.g. BTA1 and BTA21 (Taylor et al, 1998;Barendse et al, 1993), but not for others, e.g. BTA4 (Casas et al, 1999).…”
Section: Bouquet Topology Is Persistent In Male Cattle Prophase Imentioning
confidence: 99%
“…The detection of QTL for milk performance traits is still a contentious issue. Investigations carried out to date have demonstrated the presence of QTL markers on all bovine autosomes (Georges et al, 1995;Taylor et al, 1998;Mosig et al, 2001). Based on current knowledge, it may be stated that no candidate genes, responsible for the manifestation of milk performance traits, have been found in BTA1 so far.…”
mentioning
confidence: 99%